Effects of dam metabolic profile and seasonality (Spring vs. Winter) on their offspring’ metabolism, health, and immunity: maternal factors in dairy calves’ analytes - Santos, Fernanda Carolina Ramos dos; Santarosa, Bianca Paola; Dal Más, Felipe Eduardo; Silva, Karen Nascimento da; Guirro, Érica Cristina Bueno do Prado; Gomes, Viviani (Frontiers in Veterinary Science, 2024)
Maternal status during the transition period can significantly impact the health and performance of Holstein dairy calves, with lasting effects on various variables. However, the relationship between maternal late gestation metabolic status, seasonality, and their impact on offspring remains unclear. This study aimed to assess the influence of maternal variables at calving on the performance, metabolism, and immunity of 28 dairy calves during their first month of life. Blood samples were collected from 28 Holstein cows at calving. Median results for maternal variables including non-esterified fatty acids (NEFA), β-hydroxybutyrate (BHB), glucose, total protein (TP), albumin, triglycerides (TG), total cholesterol (TC), haptoglobin (Hp), body weight (BW), and body condition score (BCS) were determined. These median values served as a basis for categorizing the offspring into two groups based on their dams’ high or low degree of each maternal variable. Additionally, calves were categorized by the season of birth (Spring vs. Winter), with 14 in each. Blood samples were collected from the calves at birth and on days 1, 7, 14, and 28 to assess IgG, biochemical parameters, and haptoglobin concentration. Reactive oxygen species (ROS) production by polymorphonuclear cells stimulated by various agents was also evaluated. Clinical assessments were conducted for diarrhea and bovine respiratory disease frequencies. Despite the overall health of the cows, differences were observed in the calves between maternal groups. Heavier cows with high maternal BCS tended to have larger offspring, while high maternal BCS was associated with increased diarrhea prevalence. Low maternal BCS resulted in a stronger innate immune response, indicated by higher ROS production. Calves from cows experiencing metabolic changes during calving displayed elevated Hp concentrations. Spring-born calves were larger but had lower serum IgG concentration and reduced innate immune response compared to winter-born calves. Additionally, spring-born calves exhibited higher Hp and increased diarrhea prevalence on day 28. These findings underscore the importance of the prenatal period in determining neonatal health and suggest further research to elucidate the long-term clinical implications of maternal effects on offspring health and growth. Investigating offspring constituents later in life can provide insight into the persistence of maternal effects over time.